The genius of women : from overlooked to changing the world - Kaplan, Janice (Dutton, 2020)
"We tell girls that they can be anything, so why do 90 percent of Americans believe that geniuses are almost always men? New York Times bestselling journalist Janice Kaplan explores the powerful forces that have rigged the system--and celebrates the women geniuses past and present who have triumphed anyway. Even in this time of rethinking women's roles, we define genius almost exclusively through male achievement. When asked to name a genius, people mention Albert Einstein, Leonardo da Vinci, and Steve Jobs. As for great women? In one survey, the only female genius anyone listed was Marie Curie. Janice Kaplan, the New York Times bestselling author of The Gratitude Diaries, set out to determine why the extraordinary work of so many women has been brushed aside. Using her unique mix of memoir, narrative, and inspiration, she makes surprising discoveries about women geniuses now and throughout history, in fields from music to robotics. Through interviews with neuroscientists, psychologists, and dozens of women geniuses at work in the world today--including Nobel Prize winner Frances Arnold and AI expert Fei-Fei Li--she proves that genius isn't just about talent. It's about having that talent recognized, nurtured, and celebrated. Across the generations, even when they face less-than-perfect circumstances, women geniuses have created brilliant and original work. In The Genius of Women, you'll learn how they ignored obstacles and broke down seemingly unshakable barriers. The geniuses in this moving, powerful, and very entertaining book provide more than inspiration--they offer a clear blueprint to everyone who wants to find her own path and move forward with passion." --